Arabidopsis Polycomb Repressive Complex 2 binding sites contain putative GAGA factor binding motifs within coding regions of genes - Deng, Weiwei; Buzas, D.; Ying, H.; Robertson, M.; Taylor, J.; Peacock, W.; Dennis, E.; Helliwell, C. (2013)
Background: Polycomb Repressive Complex 2 (PRC2) is an essential regulator of gene expression that maintains genes in a repressed state by marking chromatin with trimethylated Histone H3 lysine 27 (H3K27me3). In Arabidopsis, loss of PRC2 function leads to pleiotropic effects on growth and development thought to be due to ectopic expression of seed and embryo-specific genes. While there is some understanding of the mechanisms by which specific genes are targeted by PRC2 in animal systems, it is still not clear how PRC2 is recruited to specific regions of plant genomes. Results: We used ChIP-seq to determine the genome-wide distribution of hemagglutinin (HA)-tagged FERTLIZATION INDEPENDENT ENDOSPERM (FIE-HA), the Extra Sex Combs homolog protein present in all Arabidopsis PRC2 complexes. We found that the FIE-HA binding sites co-locate with a subset of the H3K27me3 sites in the genome and that the associated genes were more likely to be de-repressed in mutants of PRC2 components. The FIE-HA binding sites are enriched for three sequence motifs including a putative GAGA factor binding site that is also found in Drosophila Polycomb Response Elements (PREs). Conclusions: Our results suggest that PRC2 binding sites in plant genomes share some sequence features with Drosophila PREs. However, unlike Drosophila PREs which are located in promoters and devoid of H3K27me3, Arabidopsis FIE binding sites tend to be in gene coding regions and co-localize with H3K27me3.